DINAMIKA ELIT LOKAL DALAM MEMPERJUANGKAN PEMEKARAN KABUPATEN INDRAGIRI SELATAN UNTUK MENJADI DAERAH OTONOM BARU TAHUN 2009-2015 - Hijri Aprianto; Tito Handoko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Regional expansion is carried out on the basis of considerations to improve services to the community, improve the management of regional potential, and improve the welfare of the community. Along with the dynamics of community development in the reform era, the phenomenon of the community's desire to form new autonomous regions (both Province, Regency/City) emerged. One of them is Indragiri Hilir Regency which will expand into South Indragiri as a new autonomous region.Indragiri Hilir Regency is considered feasible to expand, considering its very wide geographical conditions. In addition, many areas are separated by rivers so that access to the capital city as a service center is difficult to reach.This study aims to determine the dynamics of local elites in fighting for the expansion of South Indragiri Regency and to find out the feasibility of the expansion, as well as the obstacles to the expansion of South Indragiri which have not been developed until now. The Political Theory of Regional Government used in the study acts as a reinforcement so that the researcher is able to explain the research data. This study uses a qualitative approach and the type of descriptive research. Data collection techniques were carried out by means of observation, interviews and documentation.The results of this study indicate that first, the dynamics of the local elite and the community in fighting for the expansion of South Indragiri Regency have made efforts to expand their area so that the community can get more services. Second, the preparation of administrative requirements for South Indragiri Regency is ready to be expanded. This preparation must prepare human resource development efforts. Third, the slow process of division of South Indragiri Regency is caused by the moratorium on the formation of new autonomous regions (DOB) from the central government. Keywords: Local Elite, Regional Autonomy, Regional Expansion